Energy and nutrient recovery from agro-wastes: Rethinking their potential possibilities - Vaish B.; Srivastava V.; Singh P.K.; Singh P.; Singh R.P. (My University, 2025)
Agricultural sector has inescapably drawn attention towards itself due to growing concern over population explosion, changing climate and depletion of resources. Advancements in technology have caused rapid boost in farm productivity and hence huge production of agro-wastes. There have been massive deteriorating impacts of agro-wastes on existing environmental conditions, creating wide scale environmental pollution as well as biodiversity loss. Since, agro-wastes have huge potential in the form of energy and nutrient recovery (ENR), amalgamations of different technologies would promote sustainability. ENR not only adjoins an added profitable product but also facilitates to close environmental nutrient cycles. This provides a substitute to existing unsustainable approaches that are energy demanding and reliant on nonrenewable sources of energy. This review underpins why ENR from agro-waste must be key concern in production of array of higher value products. © 2020 Korean Society of Environmental Engineers.